Mosquito species distribution in mainland Portugal 2005-2008 - Osório, Hugo C. (2011)
Information on distribution and relative abundance of the mosquito fauna of mainland Portugal has been collected by several surveillance programmes and projects over a long period. The work presented here documents additional information provided by capture of adult mosquitoes by the use of CDC light traps baited with CO2 in 48 localities in 13 districts in different parts of mainland Portugal during the period 2005-2008, and by larval surveys using dippers. More than 150,000 adult mosquitoes and 3,000 larvae belonging to 16 species were identified at the National Institute of Health / Centre for Vectors and Infectious Diseases Research. The three commonest species were Ochlerotatus caspius, Culex pipiens, and Cx. theileri. The most widespread species was Cx. pipiens, followed by Culiseta longiareolata. The composition and abundance of the different mosquito populations varied between geographical locations. Only larvae of two species, Cx. hortensis and Cx. laticinctus, were found. Some effects of collection methods on a complete picture of mosquito distribution and abundance are discussed.